Content analysis of ocular pathology interventions written in the Malay Medical Manuscript of Pahang - Md Mustafa, Md-Muziman-Syah; Arifin, Muhammad Husairee; Abdul Jalal, Ahmad Farid (IIUM Press, 2023)
Introduction: A Malay medical manuscript (MMM) is a precious artefact inherited by Malay ancestors to be preserved and used as a reference in medical interventions. In recent years, MMMs have gained attention from researchers for identifying potential materials for modern clinical use. Aims: The aims of this study were to review the MMM of Pahang and to analyse its contents that are related to ocular pathology interventions. Methods: The MMM of Pahang was reviewed to identify the contents described in ocular pathology interventions. Subsequently, the contents were analysed using the Scientific Analysis of Kitab Tib Index (SAKTI), consisting of sub-indices of the Manuscript Selection (SAKTI-iMS) and the Pharmaceutical Prospectivity (SAKTI-iPharmaprospect). In comparing materials of the formulations used for ocular pathology interventions with published scientific evidence, we adapted the SAKTI subindex of the Comparison with Published Scientific Evidence (SAKTI-iComPSE). Results: The total score of the SAKTI-iMS for the MMM of Pahang was four over six. Four entries described ocular pathology interventions, including three physical approaches (for blurred vision, dry eye, and eye pain) and one non-physical approach (for conjunctivitis). For physical interventions, 12 materials were used in the formulations, five of which were found to be supported by published scientific evidence. Blurred vision and eye pain interventions scored more than nine, whereas dry eye intervention scored six for the SAKTI-iPharmaprospect. Conclusions: The findings revealed valuable insights into ocular pathology interventions, with several materials that have been scientifically proven for the treatment of targeted ocular pathologies. The integration of traditional knowledge and scientific validation underscores the potential of MMM in informing modern ocular healthcare. These results emphasise the importance of preserving cultural medical heritage for advancing evidence-based medical interventions.